Peran Kementerian Agama Kota Palembang terhadap Upaya Pencegahan Stunting - Julanto, Rujito Dwi; Antasari, Rr. Rina; Bukhori, K.A (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT  Stunting is a disorder of growth and development in children due to chronic malnutrition and recurrent infections, which is characterized by length or height below the standard of Presidential Regulation No. 27 of 2012. Stunting is a condition of growth failure in children, the growth in question includes the growth of the body and brain, due to malnutrition for a long time, so that the child is shorter than a normal child of his age and has a delay in thinking. This research aims to analyze the efforts of the Ministry of Religion of Palembang City in stunting prevention and its role in stunting prevention efforts in Palembang City. This type of research is field research, with a qualitative approach. The respondents in this study were the head of the Ministry of Religion of Palembang City, the head of the Community Guidance Division (Bimas), the head of the Religious Affairs Office (KUA), and the bride-to-be (Catin). Data collection techniques use observation, interviews, and documentation. This research found that: 1) Stunting prevention efforts carried out by the Ministry of Religion of Palembang City include a. School-Age Adolescent Guidance Program. b. Marriage Guidance Program. c. Sakinah Family Service Center Program. d. Moderation Village Program. 2) The Ministry of Religion of Palembang City plays the role of regulator, as a supervisor, coach and assessor. The Ministry of Religious Affairs of Palembang City, which oversees all KUAs in Palembang City, always synergizes in carrying out its duties in general, and stunting prevention in particular. The Islamic Guidance Sector as a Leading sector collaborates with related fields to optimize the implementation of stunting prevention programs in the city of Palembang.  Keywords: Role, Attemp, Ministry of Religion, Stunting  ABSTRAK Stunting adalah gangguan pertumbuhan dan perkembangan pada anak akibat kekurangan gizi  kronis dan infeksi berulang, yang ditandai dengan Panjang atau tinggi badannya berada dibawah standar Peraturan Presiden No 27 Tahun 2012. Stunting adalah kondisi gagal pertumbuhan pada anak, pertumbuhan yang dimaksud meliputi pertumbuhan badan dan otak, akibat kekurangan gizi dalam waktu yang lama, sehingga anak lebih pendek dari anak normal seusianya dan memiliki keterlambatan dalam berpikir. Penelitian ini bertujuan untuk menganalisis upaya Kementerian agama kota Palembang dalam pencegahan stunting dan perannya terhadap upaya pencegahan stunting di Kota Palembang. Jenis penelitian ini adalah penelitian lapangan (field research), dengan pendekatan kualitatif. Respondendalam penelitian ini adalah kepala Kementrian Agama Kota Palembang, kepala Bidang Bimbingan Masyarakat (Bimas), kepala Kantor Urusan Agama (KUA), dan calon pengantin (Catin). Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Peneletian ini menemukan bahwa: 1) Upaya pencegahan stunting yang dilakukan oleh Kementerian Agama Kota Palembang meliputi a. Program Bimbingan Remaja Usia Sekolah. b. Program Bimbingan Perkawinan. c. Program Pusat Layanan Keluarga Sakinah. d. Program Kampung Moderasi. 2) Kementerian Agama Kota Palembang berperan sebagai pengatur regulasi, sebagai pengawas, pembina dan penilai. Kemenetrian Agama Kota Palembang yang menaungi seluruh KUA yang ada di Kota Palembang senantiasa bersinergi dalam melaksanakan tugas-tugasnya secara umum, dan pencegahan stunting secara khusus. Bidang Bimas Islami sebagai Leading sektor berkerjasama dengan bidang terkait untuk mengoptimalkan pelaksanaan program pencegahan stunting di Kota Palembang.  Kata Kunci: Peran, Upaya, Kementrian Agama, Stunting.